Análisis of the vascular sounds of the arteriovenous fistula - Munguía Mena, Marco A.; Tutor: Espinoza Paniagua, Yara (Lund University UNI, 2011)
This licenciate thesis is in the field of biomedical signal porcessing with main focus on processing of the vascular rounds of the hemodialisys vascular access in patient undergoing hemodialyisis.
Tesis (Licentiate of Engineering) - UNI, 2011.
Keywords: INGENIERÍA BIOMEDICA; TECNOLOGIA MÉDICA